Research Perspectives on the Regulation and Physiological Functions of FGF21 and its Association with NAFLD - Inagaki, Takeshi (Frontiers in Endocrinology, 2015)
Fibroblast growth factor 21 (FGF21) is a metabolic hormone primarily secreted from the liver and functions in multiple tissues. Various transcription factors induce FGF21 expression in the liver, which indicates that FGF21 is a mediator of multiple environmental cues. FGF21 alters metabolism under starvation conditions, protects the body from energy depletion, and extends life span. Pharmacological administration of FGF21 alleviates dyslipidemia and induces weight loss in obese animals. In addition to the well-studied functions of FG21, several lines of recent evidence indicate a possible link between FGF21 and nonalcoholic fatty liver disease (NAFLD). High serum levels of FGF21 are associated with NAFLD and its risk factors such as endoplasmic reticulum stress and chronic inflammation. In addition, FGF21 alleviates the major risk factors of NAFLD including obesity, dyslipidemia and insulin insensitivity. Thus, FGF21 is a potential drug candidate for diseases such as NAFLD, dyslipidemia, and type 2 diabetes. In this review, the research perspectives of FGF21 and therapeutic potencies of FGF21 as a modulator of NAFLD are summarized.